Penegakan Hukum Terhadap Pelaku Pornografi Dalam Aplikasi Mango - Hehakaya, Grand Nehemia; Supusepa, Reimon; Latumaerissa, Denny (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Social media is a medium for online communication, allowing people to interact without the constraints of time and space. However, this lack of boundaries often leads some people to commit various crimes, one of which is pornography. The case studied involved an application called Mango, which became a platform for pornography perpetrators to carry out their actions, starting with indecent acts involving adult scenes watched live streamed to earn coins to be monetized, thus becoming a business opportunity for these perpetrators. Therefore, pornography crimes through the Mango application must be viewed in accordance with the legal provisions concerning pornographic activities contained in the Pornography Law, namely Law No. 44 of 2008, followed by the ITE Law, namely Law No. 11 of 2008. The formulation of the problem is law enforcement against perpetrators of pornography in the Mango application and the forms of pornographic acts in the Mango application.Purposes of the Research: This study aims to analyze and discuss law enforcement against perpetrators of pornography in the Mango application. Methods of the Research: The research method used is a normative juridical research type. The approach to the problem of legislation, conceptual analysis, and sources of legal material used include primary and secondary legal materials. Data collection techniques include literature review, followed by descriptive analysis using quantitative methods.Results / Findings / Novelty of the Research: The research results indicate that the freedom granted to social media users has led to numerous criminal offenses, particularly pornography. Therefore, it is appropriate for Mango users to be subject to criminal law enforcement. Furthermore, considering the forms of pornographic acts in the Mango application, a more mature policy is needed to handle existing cases, given the weakness of the cyber system in Indonesia.